Group-based Cognitive Behavioural Therapy for Anxiety Disorder in Children with Autism Spectrum Disorder: a feasibility study. (4th July 2019) - Kilburn, Tina R.; Juul Sørensen, Merete; Thastum, Mikael; Rapee, Ronald M.; Rask, Charlotte Ulrikka; Bech Arendt, Kristian; Thomsen, Per Hove
Abstract: Purpose: Autism spectrum disorder (ASD) includes core symptoms that affect general and social development. High risk of developing comorbid disorders such as anxiety is prominent. Up to 60% of children with ASD suffer from anxiety disorders which can negatively influence educational, social and general development together with quality of life. This study is the first to investigate the feasibility of the manualised cognitive behavioural therapy (CBT) group programme 'Cool Kids ASD' for anxiety adapted for children with ASD in a general hospital setting. Methods: Nine children, aged 9–13 years, with ASD and anxiety recruited from a public child psychiatric health clinic were enrolled in the study. Outcome measures were collected from both child and parent pre- and post-treatment and at 3-month follow-up and included scores from a semi-structured anxiety interview, together with questionnaires on anxiety symptoms, life interference, children's automatic thoughts and satisfaction with the programme. Results: Eight out of nine families found the programme useful and would recommend it to other families in a similar situation. Six families attended all 12 sessions in the programme, two missed one session and one family only managed to attend eight sessions. At follow-up, five children were free of all anxiety diagnoses and a further two out of the nine children no longer met the criteria for their primary anxiety diagnosis. Conclusions: This study suggests that the transition of the group programme 'Cool Kids ASD' from University Clinics to standard child psychiatric clinical settings is feasible. Further randomised studies are needed to confirm the efficacy of the programme in a larger sample.